2019
DOI: 10.1186/s40168-019-0716-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between pneumococcal vaccination, ethnicity, and the nasopharyngeal microbiota of children in Fiji

Abstract: Background Streptococcus pneumoniae is a significant global pathogen that colonises the nasopharynx of healthy children. Pneumococcal conjugate vaccines, which reduce nasopharyngeal colonisation of vaccine-type S. pneumoniae , may have broader effects on the nasopharyngeal microbiota; however, data are limited. In Fiji, nasopharyngeal carriage prevalence of S. pneumoniae and other colonising species differ between the two main et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 61 publications
5
28
1
Order By: Relevance
“…The significant proportion of individuals who harbour profiles that are being considered to be potentially protective either in terms of acute respiratory infections 55 or chronic disease such as asthma 56 – 58 , is intriguing. Similar profiles were observed in Fijian children with either Dolosigranulum or Haemophilus / Corynebacterium dominant profiles 53 although there are important contrasts, remembering that these were observed in older children and adults, we observed Corynebacterium and Corynebacterium / Dolosigranulum profiles in the Orang Asli. Lastly, while Delftia is not uncommon as an oral bacterium 59 , given the common finding of Delftia and Ochrobactrum as contaminants in microbiome research 60 we interpret these four samples with extreme caution.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The significant proportion of individuals who harbour profiles that are being considered to be potentially protective either in terms of acute respiratory infections 55 or chronic disease such as asthma 56 – 58 , is intriguing. Similar profiles were observed in Fijian children with either Dolosigranulum or Haemophilus / Corynebacterium dominant profiles 53 although there are important contrasts, remembering that these were observed in older children and adults, we observed Corynebacterium and Corynebacterium / Dolosigranulum profiles in the Orang Asli. Lastly, while Delftia is not uncommon as an oral bacterium 59 , given the common finding of Delftia and Ochrobactrum as contaminants in microbiome research 60 we interpret these four samples with extreme caution.…”
Section: Discussionsupporting
confidence: 79%
“…A similar interaction may also explain the absence of Streptococci 50 —although we recognise in both cases that our hypothesis requires further testing due to the identification of both S. aureus and pneumococcal carriage among our participants. A Moraxella dominated profile similar to CST6, is also present in the Orang Asli, a profile which has also been observed in healthy adults in a European setting 51 , as well as in both Kenyan 52 and Fijian children 53 (where it is more common in iTaukei, the indigenous Fijians). We also saw a Moraxella - Haemophilus profile which hasn’t been described previously.…”
Section: Discussionsupporting
confidence: 52%
“…However, the top 15 most abundant OTUs in our study contained several bacteria that are not commonly observed in developed regions, including multiple Acinetobacter species. Interestingly, other studies performed in populations that reside in humid tropical regions also reported Acinetobacter presence in the upper respiratory tract of young children [ 25 , 26 ], most likely because wet environments, such as moist soil, water plants, and seawater, are known environmental reservoirs for Acinetobacter [ 27 ]. This suggests a location-specific bacterial colonization pattern, which might have important implications for preventive and therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several of the bacteria that were associated with the absence of RTIs included environmental bacteria not commonly observed in developed regions such as Acinetobacter , Caulobacteraceae , and Pseudomonas . A recent study in young Fijian children residing on a tropical island also reported Pseudomonas to be abundantly present in the nasopharynx of healthy children [ 26 ]. Like Acinetobacter , Pseudomonas is present in watery environments, particularly in rivers during the period just before heavy rainfalls that lead to an influx of water into the river [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…NP swabs were collected from 132 total children belonging to the two ethnic groups that were further divided in two subgroups based on whether children had been previously vaccinated or not with PCV-7. The vaccination had no overall impact on microbial diversity or composition, but significant modifications were evident when stratifying by ethnicity: vaccinated iTaukei children had a lower relative abundance of Streptococcus and Haemophilus compared with unvaccinated ones, while vaccinated Indian descent children had a higher relative abundance of Dolosigranulum compared with those unvaccinated [55].…”
Section: Pneumococcal Vaccinationmentioning
confidence: 92%